One Name – One Fungus: The Influence of Photosynthetic Partners on the Taxonomy and Systematics of Lichenized Fungi - Martin Kukwa; Magdalena Kosecka; Beata Guzow-Krzemińska (Acta Societatis Botanicorum Poloniae, 2020)
Lichens are fungi (mycobionts) that form symbiotic associations with photoautotrophic prokaryotes or eukaryotes (photobionts); however, some species can exchange photosynthetic partners during their lifecycles. This phenomenon modifies the morphology of lichens and consequently influences the taxonomy of lichenized fungi. Here, a few such cases in which the photobionts influenced the taxonomy and systematics of lichenized fungi are reviewed. Two different morphotypes of the same species – known as photomorphs – were classified as different species and sometimes different genera. Moreover, different types of photobionts and the absence or presence (optional lichenization) of an alga in the thallus were believed to be diagnostic characters for discriminating genera. However, the taxonomy and systematics of lichens are based always, according to Article F.1.1. of the International Code of Nomenclature for Algae, Fungi, and Plants, on the fungal partner and only one name is applied.